2004
DOI: 10.1182/blood-2003-09-3081
|View full text |Cite
|
Sign up to set email alerts
|

Bone loss following hematopoietic stem cell transplantation: a long-term follow-up

Abstract: Transplantation-associated bone loss is a well-known phenomenon, however, effects of hematopoietic stem cell transplantation are insufficiently characterized. We conducted a prospective, unicentric, longterm follow-up in 280 patients undergoing allogeneic hematopoietic stem cell transplantation (HSCT). Bone mineral density (BMD) was measured before transplantation and then yearly for at least 4 years. Patients received vitamin D plus calcium until steroid withdrawal. Mean baseline BMD was normal. We demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
92
5
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 41 publications
5
92
5
2
Order By: Relevance
“…The association between glucocorticoids and bone loss at various sites has been inconsistent in previous studies. [1][2][3][4][5] The lack of association with spine BMD loss in our study is unexpected as trabecular bone loss occurs most rapidly in glucocorticoid-induced osteoporosis. 8 At the more cortical site, the femoral neck, the lack of association suggests that cortical bone loss occurs by a distinct mechanism.…”
contrasting
confidence: 45%
See 3 more Smart Citations
“…The association between glucocorticoids and bone loss at various sites has been inconsistent in previous studies. [1][2][3][4][5] The lack of association with spine BMD loss in our study is unexpected as trabecular bone loss occurs most rapidly in glucocorticoid-induced osteoporosis. 8 At the more cortical site, the femoral neck, the lack of association suggests that cortical bone loss occurs by a distinct mechanism.…”
contrasting
confidence: 45%
“…2,3 Declines in BMD are greater at the femoral neck, a site rich in cortical bone, than lumbar spine, a site rich in trabecular bone, and this may suggest disproportionate cortical bone loss. 1,[3][4][5] This pattern is unlike the early spine BMD decline generally seen in postmenopausal and glucocorticoid-induced osteoporosis and suggests a unique mechanism. In addition, qualitative microstructural properties also affect bone strength and fracture risk.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…In a study of long term follow up of bone loss after BMT, Schulte and Beelen observed that lumbar spine BMD begins to recover after 12 months, returning to baseline at 48 months (24). High levels of bone marrow interleukin-6 during the immediate post-BMT period were related to the bone loss.…”
Section: Bone Marrow Transplantationmentioning
confidence: 99%